Solving mathematical problems in students with and without intellectual giftedness - Rocha, Alberto (2021)
The analysis of the mathematical performance of the students favors the adjustment and individualization of the educational processes for this area of learning. Due to its relevance in daily life, the teacher must bear in mind the functionality and transfer of mathematical learning. The generalization of research that combines theory and practice is essential. In this sense, there are few studies at the curriculum level for mathematics related to the education of gifted and/or mathematically talented students. Thus, it becomes pertinent to analyze such mathematical skills and the factors in which these students stand out. The purpose of this study is to analyze the types of mathematical reasoning and representations based on problem-solving tasks expressed by gifted students on an educational level with a good performance in the area of Mathematics. Forty-two students were evaluated as gifted, and were compared with 52 high-performance students in terms of age and school year (10-15 years old). The existence of statistically significant differences in certain tasks and representations was verified, with the schoolchildren with the greatest potential showing more complex representations and more elaborate reasoning. Knowing the nature of the potentialities favors the individualization of the educational processes.